Update on the management of osteoarthritis - Goh, Emily M.L.; Chow, S.K.; Yeap, S.S. (Faculty of Medicine, University of Malaya, 2002)
Osteoarthritis is the most common joint disorder in the human population. It is characterized by the destruction of articular cartilage and the overgrowth of marginal and subchondral bone. The commonest weight bearing joint affected is that of the knee, affecting over one third of people over the age of 65 years. This article reviews the recent principles of non surgical management of osteoarthritis. This is divided into non drug management such as primary prevention, physiotherapy, occupational therapy and patient education. Drug management will include the use of different types of analgesics, viscosupplementation as well as joint injection.